Ancient copper mines as geotourist and archeological objects in the southern Ural Mts. - Pawlikowski, Maciej; Pieprzyk-Klimaszewska, Karolina; Mikoś, Tadeusz (Geotourism/Geoturystyka, 2018)
The main aim of this paper is to present to the Readers the southern part of the Ural Mts. including geography, geology and abundatn mineral deposits. Moreover, the authors describe poorly known, ancient copper mining and processing centers in the vicinity of Kargaly, where intensive archaeological excavations are recently carried on. In old, watered copper mines the animal bones mineralized with copper compounds were encountered. Samples were examinated in the laboratories of the AGH-Univesity of Science and Technology in Kraków. It was found that bones have been mineralized with copper solutions for thousands of years. Bones belong to fragile materials. A long-lasting mineralization resulted in a noticeable changes in physico-mechanical parametres The Southern Ural Mts., including the area of Kargaly can be an interesting region for geotourists and for any other persons who would like to gain knowledge on geology, mining engineering and/or archeology.